Three-Factor CAPM Risk Exposures: Some Evidence from Malaysian Commercial Banks - Aisyah Abdul Rahman (Asian Academy of Management Journal of Accounting and Finance, 2010)
This study investigates the determinants of the three-factor capital asset pricing model (CAPM) risk exposures in the case of commercial banks. Five risk exposures are examined namely, market, interest rate, exchange rate, total, and unsystematic risk exposures. Our findings provide four major contributions. First, we find that different types of risk exposures have different determinants. Second, the market risk exposure for the Islamic bank in our study is lower than for conventional banks. Third, the merger programme is fruitful because it reduces the interest rate risk exposure, total risk exposure, and unsystematic risk exposure. Finally, our results show that the banks under study have higher total and unsystematic risk exposures during the 1997 Asian financial crisis. Thus, a clear understanding of this evidence helps in ensuring effective and successful decision-making for regulators, policy makers and market players.